Substitute Heirs : An Overview From Perception And Role Of Ustad In Bengkulu, Indonesia - Yusmita Yusmita (Fakultas Syariah UIN Fatmawati Sukarno Bengkulu, 2023)
Legal rules regarding substitute heirs are regulated in Article 183 of the Compilation of Islamic Law, which stipulates that heirs who die earlier than heirs can be replaced by their children. Ideally, this rule of law has been disseminated to the community. Ustadz is an officer who directly delivers Islamic laws to the community. The type of this research is descriptive-qualitative research. The research subjects were Ustad who gave religious lectures to taklim assembly in Bengkulu City and the congregation of the taklim assembly. Data collection techniques using interviews. From the results of the study, it can be seen that the majority of Ustad in Bengkulu City do not master Islamic inheritance material, especially the rules regarding substitute heirs. Because of that they rarely convey inheritance material to the public. Regarding the role of Ustad in Bengkulu City in socializing the rules for substitute heirs, they have not played much of this due to several factors. The first factor is that they don't know much about the Islamic inheritance system, especially about the rules of surrogate heirs. Because of that, they did not convey this material to the public. The second factor, the community did not ask them about inheritance problems because they were not interested in studying it more deeply. The third factor, most people use adat in resolving the distribution of inheritance, and if there is a dispute, it is resolved by custom, then the Islamic inheritance rules regarding inheritance distribution, especially substitute heirs, are not a requirement for Bengkulu City Muslims. The institution responsible for disseminating legal regulations that regulate Indonesian Muslims is the Ministry of ReligionAturan hukum tentang ahli waris pengganti diatur pada pasal 183 Komplasi Hukum Islam, yang menetapkan ahli waris yang meninggal lebih dahulu dari pada sipewaris maka kedudukannya dapat digantikan oleh anaknya. Idealnya aturan hukum ini sudah disosialisasikan kepada masyarakat. Ustadz merupakan petugas yang secara langsung menyampaikan hukum-hukum Islam ke pada masayarakat. Adapun jenis penelitian ini adalah penelitian deskripitif-kualitatif. Subjek Penelitian yaitu Ustadz yang memberikan ceramah agama kepada Majlis Taklim di Kota Bengkulu, dan Jama’ah Majlis Taklim. Teknik pengumpulan data menggunakan Wawancara. Dari hasil penelitian dapat diketahui bahwa Ustadz di Kota Bengkulu mayoritas tidak menguasai materi waris Islam, terutama aturan tentang ahli waris pengganti. Karena itu mereka jarang menyampaikan materi waris kepada masyarakat. Mengenai peran para Ustadz di Kota bengkulu dalam mensosialisasikan aturan ahli waris pengganti, mereka belum banyak berperan hal ini disebabkan beberapa faktor. Faktor pertama, karena mereka tidak banyak mengetahui tentang sistem kewarisan Islam terutama tentang aturan ahli waris pengganti. Karena itu materi ini, tidak meraka sampaikan kepada masyarakat. Faktor kedua, masyarakat tidak menanyakan permasalahan waris kepada mereka karena itu mereka tidak tertarik untuk mempelajarinya lebih dalam. Faktor ketiga, masyarakat kebanyakan mempergunakan adat dalam menyelesaikan pembagian waris, dan apabila ada sengketa, maka diselesaikan dengan cara adat, maka aturan waris Islam tentang pembagian waris khususnya ahli waris pengganti tidak menjadi kebutuhan umat Islam Kota Bengkulu.Lembaga yang bertanggung jawab dalam mensosialisasikan peraturan hukum yang mengatur umat Islam Indonesia adalah Kementerian Agama